Clerodendrum inerme Leaf Extract Alleviates Animal Behaviors, Hyperlocomotion, and Prepulse Inhibition Disruptions, Mimicking Tourette Syndrome and Schizophrenia. (15th July 2012) - Chen, Hon-Lie; Lee, Hsin-Jung; Huang, Wei-Jan; Chou, Jui-Feng; Fan, Pi-Chuan; Du, Jung-Chieh; Ku, Yuan-Ling; Chiou, Lih-Chu
Abstract : Previously, we found a patient with intractable motor tic disorder, a spectrum of Tourette syndrome (TS), responsive to the ground leaf juice of Clerodendrum inerme ( CI ). Here, we examined the effect of the ethanol extract of CI leaves ( CI extract) on animal behaviors mimicking TS, hyperlocomotion, and sensorimotor gating deficit. The latter is also observed in schizophrenic patients and can be reflected by a disruption of prepulse inhibition of acoustic startle response (PPI) in animal models induced by methamphetamine and NMDA channel blockers (ketamine or MK-801), based on hyperdopaminergic and hypoglutamatergic hypotheses, respectively. CI extract (10–300 mg/kg, i.p. ) dose-dependently inhibited hyperlocomotion induced by methamphetamine (2 mg/kg, i.p. ) and PPI disruptions induced by methamphetamine, ketamine (30 mg/kg, i.p. ), and MK-801 (0.3 mg/kg, i.p. ) but did not affect spontaneous locomotor activity, rotarod performance, and grip force. These results suggest that CI extract can relieve hyperlocomotion and improve sensorimotor gating deficit, supporting the therapeutic potential of CI for TS and schizophrenia.